Practical Imaging Informatics Foundations and Applications for PACS Professionals - Branstetter, Barton F.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Attention SIIM Members: a special discount is available to you; please log in to the SIIM website at www.siimweb.org/pii or call the SIIM office at 703-723-0432 for information on how you can receive the SIIM member price of $59.95. Imaging Informatics Professionals (IIPs) have come to play an indispensable role in modern medicine, and the scope of this profession has grown far beyond the boundaries of the PACS. A successful IIP must not only understand the PACS itself, but also have knowledge of clinical workflow, a base in several medical specialties, and a solid IT capability regarding software interactions and networking. With the introduction of a certification test for the IIP position, a single source was needed to explain the fundamentals of imaging informatics and to demonstrate how those fundamentals are applied in everyday practice. Practical Imaging Informatics describes the foundations of information technology and clinical image management, details typical daily operations, and discusses rarer complications and issues. Written by world-renown experts from the Society for Imaging Informatics in Medicine, this book is an indispensable reference for the practicing IIP, those studying for a certification exam, and any professional who needs quick access to the nuts and bolts of imaging informatics.
Technology: Getting Started -- Medical Imaging Modalities and Digital Images -- Computers and Networking -- to PACS -- Modalities and Data Acquisition -- Technology: The PACS Imaging Chain -- Workflow Steps in Radiology -- Standards and Interoperability -- Viewing Images -- Image Postprocessing and Volume Rendering -- Image Distribution -- Reporting and Dictation -- Operations: Everyday PACS -- Customer Relations -- User Training -- Quality Assurance for Medical Imaging -- Data Storage and Disaster Recovery -- Downtime Procedures and Departmental Policies -- Operations : Infrastructure and Environment -- Reading Room Design -- Workflow Testing and Workflow Engineering -- Policy Management and Regulatory Compliance -- Billing and Coding -- Strategy and Vision: Preparing for PACS -- Economics of PACS and Related Systems -- PACS Readiness -- Choosing a Vendor -- Acceptance Testing -- Strategy and Vision: PACS Administration -- Working with Vendors -- Team Building and Project Management -- Long-Range Planning.
Keywords: Medicine; Medical records -- Data processing; Radiology, Medical; Medicine & Public Health; Imaging / Radiology; Health Informatics